Experimental and numerical study on CFRP strip strengthened clay brick masonry walls subjected to vented gas explosions - Li, Zhan; Chen, L.; Fang, Q.; Chen, Wensu; Hao, Hong; Zhu, R.; Zheng, K. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
© 2019 Elsevier Ltd A total of nine full-scale field blast tests were conducted in a specially designed reinforced concrete (RC) chamber to investigate the performance of carbon fiber reinforced polymer (CFRP) strip strengthened clay brick masonry walls subjected to vented gas explosions. Three wall specimens, i.e. unstrengthened, strengthened with distributed layout and strengthened with concentrated layout were prepared for blast tests. The testing data including overpressure time histories of vented gas explosions, displacement time histories, damage modes of each wall specimen were recorded and analyzed. It was found that under vented gas explosions, the wall specimen strengthened with concentrated layout showed improved blast resistance and all three wall specimens experienced typical flexural damage. Detailed micro models for masonry walls were developed in LS-DYNA, incorporating material parameters obtained from material tests. The accuracy of numerical models in predicting the responses of masonry walls was validated with the testing data. Parametric studies were conducted to explore the performances of masonry walls with different heights and thicknesses under blast loads specified by design codes. It was found that with the increase of wall thickness or the decrease of wall height, the maximum displacement and damage level of masonry walls decreased significantly. The 115 mm-thick masonry walls needed be strengthened to prevent collapse under the specified blast loads. The strengthened walls experienced typical flexural response and the strengthening effectiveness of using CFRP, GFRP and spray-on polyurea were numerically compared.